Utilization of the Environment as A Learning Resource for Social Studies - Huriyah Huriyah (ESE International Journal (Environmental Science and Engineering), 2020)
The interaction between humans and the environment in utilizing the environmental potential as a source of social studies learning. The purpose of this study was to determine the use of the environment as a learning resource for social studies. The research method used is a qualitative research method with the type of literature. Data collection is taken from the search for library materials following the research carried out, then analyzed based on theory. The results of this study are to improve students' memory according to experience, renewable learning resources, social studies learning to be meaningful and memorable, provision of abilities for students in living life. This study concludes that the environment can be used as a source of social studies learning because it relates to the natural environment and the social environment so that it can foster a sense of love for the environment.